Microbial Contamination of the Gut; another Feature of Malnutrition - Michael Gracey; Suharjono Suharjono; Sunoto Sunoto; Delys E. Stone (Indonesian Pediatric Society, 1975)
The microbial flora of the stomach and upper small intestine was studied in 21 malnourished Indonesian children with diarrhoea and compared with that found in 21 Australian children of Caucasian extraction with a variety of alimentary disorders. In the Indonesian children there was marked microbial contamination of the upper gastrointestinal tract with a wide variety of microorganisms. In several patients there was significant overgrowth by Candida sp. and in several others large numbers of anaerobic bacteria were isolated. It is suggested that these microbiological abnormalities are related to the pathogenesis of diarrhoea in children with malnutrition.